'Caprices' and Naming in Cyrano's Letters. (1st November 2013) - Turner, Sophie
Abstract : This article explores Cyrano de Bergerac's letters and the various names that appear as their addressees and signatories. It argues that the playful nature of those names is key to the presentation of his collection as an œuvre épistolaire rather than merely as a published correspondence. Moreover, it argues that although the names that appear in the œuvre, notably the names of the addresses of the most polemical letters, can be elucidated in relation to Cyrano's biography, such lectures à clé are reductive and overlook the literary dimensions to the names themselves, the techniques of naming he employs and invents, and their effects.